Promotion of mature angiogenesis in ischemic stroke by Taohong Siwu decoction through glycolysis activation - Tang, Linfeng; Liu, Zhuqing; Ji, Zhaojie; Zhang, Xueting; Zhao, Mengdie; Peng, Daiyin; Han, Lan (Frontiers in Pharmacology, 2024)
Mature angiogenesis plays a critical role in improving cerebral ischemia-reperfusion injury (CIRI). Glycolysis serves as the primary energy source for brain microvascular endothelial cells (BMECs), whereas other vascular cells rely on aerobic respiration. Therefore, intercellular variations in energy metabolism could influence mature angiogenesis. Taohong Siwu Decoction (THSWD) has demonstrated efficacy in treating ischemic stroke (IS), yet its potential to promote mature angiogenesis through glycolysis activation remains unclear. Methods: In this study, we established a middle cerebral artery occlusion/reperfusion (MCAO/R) model in vivo and an oxygen-glucose deprivation/reoxygenation (OGD/R) model in vitro. We assessed neuroprotective effects using neurobehavioral scoring, 2,3,5-triphenyltetrazolium chloride (TTC) staining, Hematoxylin-eosin (HE) staining, and Nissl staining in MCAO/R rats. Additionally, we evaluated mature angiogenesis and glycolysis levels through immunofluorescence, immunohistochemistry, and glycolysis assays. Finally, we investigated THSWD's mechanism in linking glycolysis to mature angiogenesis in OGD/R-induced BMECs.In vivo experiments demonstrated that THSWD effectively mitigated cerebral damage and restored neurological function in MCAO/R rats. THSWD significantly enhanced CD31, Ang1, PDGFB, and PDGFR-β expression levels, likely associated with improved glucose, pyruvate, and ATP levels, along with reduced lactate and lactate/pyruvate ratios. In vitro findings suggested that THSWD may boost the expression of mature angiogenesis factors (VEGFA, Ang1, and PDGFB) by activating glycolysis, increasing glucose uptake and augmenting lactate, pyruvate, and ATP content, thus accelerating mature angiogenesis. Conclusion: THSWD could alleviate CIRI by activating the glycolysis pathway to promote mature angiogenesis. Targeting the glycolysis-mediated mature angiogenesis alongside THSWD therapy holds promise for IS treatment.